Effectiveness of Global Advertisements on Indian Culture - Srivastava, R. K. (Indian Journal of Marketing, 2009)
The World is becoming a common market place in which people, no matter where they live, desire the same products and life style was a theory propounded by Levitt in 1983. This led to the thought of transforming the world into a homo cultural market place. It is presumed that customers can be persuaded by the same advertising appeals and value irrespective of the culture they belong to. Brand and brand image could be standardized without any problem across countries. This could lead to significant saving in producing advertisements. According to Dahl (2005), it could also lead to saving of time and money with respect to cost of design. Most multinational companies feel that international brands should create a global image. By purchasing it, they will receive the same benefits whether it be life style, status, convenience or financial. Global consumer culture positioning (GCP) through a recognized set of symbols can enhance meaningful advertisement (Alden et. al, 1999). Standardized advertisement based on multi-cultural segment can be implemented (Gram 2007). Global advertisement in the world is particularly found in Luxury products, cosmetics, perfumes, and watches (Belche and Belche, 1998).